PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK EKSPERIMEN FISIKA BERBASIS KEARIFAN LOKAL UNTUK SEKOLAH MENENGAH PERTAMA - Jumadi; Darmadi , I Wayan; Darsikin (Universitas Tadulako, 2021)
The research aims to produce a comic of physics experiments based on local wisdom. The research uses the development of 4D models, which begins with defining the material, designing the media until it becomes a product. Once it becomes a product it is then validated by material experts and media experts. Comics that have been validated by some experts are then revised by researchers about the advice given by validators. To create this comic, researchers used Photoshop and Coreldraw X7 applications. This experimental comic is designed so that students can conduct simple experiments outside the school independently on temperature and heat material, in addition, this comic features the icon of Palu city along with the story that develops on the icon. The subject of the research trial of the feasibility of this physics experiment comic is the students of class VII junior high school Lab school Palu. The average score obtained is 3.71 with excellent category. The results showed that this experimental comic can be used as a medium of learning.